1983
DOI: 10.1161/01.hyp.5.4.615
|View full text |Cite
|
Sign up to set email alerts
|

Captopril stimulation of differential renins in renovascular hypertension.

Abstract: SUMMARY Twenty-six patients being evaluated for renovascular hypertension were studied to assess the diagnostic value of enhancing the differential between renal venous renins (PRA) by a single 25 mg oral dose of converting enzyme inhibitor (CEI, captopril). Antihypertensive medications were not discontinued prior to the study, and renal venous effluent was sampled before and 30 minutes after CEI. Eight patients without stenosis who did not have surgery had post-CEI ratios of less than 3.0. The other 18 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0
1

Year Published

1985
1985
2005
2005

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(9 citation statements)
references
References 19 publications
0
8
0
1
Order By: Relevance
“…3 Though the comparison of renal vein renin activity in each kidney is quite sensitive, especially in patients with unilateral renal artery stenosis and normal renal function, it is not sufficiently accurate in patients with bilateral disease or renal insufficiency. 34 Therefore, we and others have advocated proceeding directly to arteriography as the sole diagnostic procedure in patients believed, on clinical grounds, to have a high likelihood of renal artery stenosis.…”
mentioning
confidence: 99%
“…3 Though the comparison of renal vein renin activity in each kidney is quite sensitive, especially in patients with unilateral renal artery stenosis and normal renal function, it is not sufficiently accurate in patients with bilateral disease or renal insufficiency. 34 Therefore, we and others have advocated proceeding directly to arteriography as the sole diagnostic procedure in patients believed, on clinical grounds, to have a high likelihood of renal artery stenosis.…”
mentioning
confidence: 99%
“…The renal vein renin ratio peaked at 30 minutes after oral captopril with a (right/left) ratio of 4.3:1, compatible with that observed in patients with renin-dependent renovascular stenosis (Ͼ3:1 under similar conditions). 19 The rapid decrease in the plasma aldosterone concentration confirmed that angiotensin II blockade was achieved by the captopril. The patient's blood pressure decreased concurrently with administration of the captopril and remained suppressed for 4 to 6 hours.…”
Section: Patientmentioning
confidence: 69%
“…Confirmation would then be performed by measuring stimulated renal vein renins as previously published. 19 Because of dilutional effects from the ipsilateral normally perfused segments, it would be important to either obtain segmental venous effluent renins 24 and/or use efforts to maximally stimulate the abnormal segment while the renin released from the normal segments is still suppressed. This may be difficult to achieve in those patients on long-term diuretic therapy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations